Hybrid Learning 4th International Conference, ICHL 2011, Hong Kong, China, August 10-12, 2011. Proceedings - Kwan, Reggie; Fong, Joseph; Kwok, Lam-for.; Lam, Jeanne; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Hybrid Learning, ICHL 2011, held in Hong Kong, China, in August 2011. The 32 contributions presented in this volume were carefully reviewed and selected from numerous submissions. In addition two keynote talks are included in this book. The topics covered are practices in borderless education, pedagogical issues and practice, organizational frameworks for hybrid learning, experiences in hybrid learning, computer supported collaborative learning, and interactive hybrid learning systems.
Keywords: Computer science; Artificial intelligence; Computer simulation; Social sciences -- Data processing; Education; Computer Science; Computation by Abstract Devices; Artificial Intelligence (incl. Robotics).; Simulation and Modeling; Computers and Education; User Interfaces and Human Computer Interaction; Computer Appl. in Social and Behavioral Sciences